EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DAN NUMBERED HEADS TOGETHER (NHT) DITINJAU DARI KEMANDIRIAN BELAJAR PADA PRESTASI BELAJAR MATEMATIKA PESERTA DIDIK SMA SE – KAB. MAGELANG TAHUN PELAJARAN 2012/2013 - Pratiwi, Katherine Her; Budiyono, Budiyono; Subanti, Sri (Jurnal Pembelajaran Matematika, 2013)
ABSTRACT: The objectives of this research are to investigate: 1) which of the cooperative learning model of the Jigsaw type, the cooperative learning model of the Numbered Heads Together (NHT), and the direct learning  results in a better learning achievement in mathematics, 2) which of  the students with the high self-regulated learning, the students with the medium self-regulated learning, and the students with the low self-regulated learning have a better learning achievement in mathematics, 3) in each of the learning models which of the students with the high self-regulated learning, the students with the medium self-regulated learning, and the students with the low self-regulated learning have a better learning achievement in mathematics, 4) in each of the self-regulated learning, which on the cooperative learning model of the Jigsaw type, the cooperative learning model of the NHT type, and the direct learning model results in a better learning achievement in mathematics. The research used the experimental quasi research method with the factorial design of 3x3. The population of the research was all of the students in Grade XI of Senior High School  in Magelang regency in academic year 2012/2013. The samples of research were taken by using the stratified cluster random sampling. The samples of the research were the students of Taruna Nusantara senior high school, state senior high school 1 of Bandongan, and state senior high school 1 of Dukun. The hypotheses of the research were analyzed by using the two-way analysis of variance with unbalanced cells at the significance level of a = 0,05. The results of the research are as follows: 1) Jigsaw better than NHT and direct learning, whereas NHT equal to direct learning in mathematics achievement, 2) the high self-regulated learning better than medium  and low, whereas the medium better than low in mathematics achievement, 3) Jigsaw with the high self-regulated learning better than the medium and low, whereas the medium better than the low in mathematics achievement. NHT with the high self-regulated learning better than the medium and low, whereas the medium equal to the low in mathematics achievement. Direct learning with the high self-regulated learning better than the medium and low, whereas the medium equal to the low in mathematics achievement. 4) The high self-regulated learning with the cooperative learning model of NHT type better than Jigsaw and direct learning, whereas Jigsaw better than direct learning. The medium self-regulated learning with the cooperative learning model of Jigsaw type better than NHT and direct learning, whereas NHT equal to direct learning. The Low self-regulated learning with NHT better than Jigsaw and direct learning in mathematics achievement. Keywords : Jigsaw, NHT, and self-regulated learning.